Companion of the the Web Conference 2018 on the Web Conference 2018 - WWW '18 2018
DOI: 10.1145/3184558.3186337
|View full text |Cite
|
Sign up to set email alerts
|

The Grass is Greener on the Other Side

Abstract: Green spaces are believed to improve the well-being of users in urban areas. While there are urban research exploring the emotional benefits of green spaces, these works are based on user surveys and case studies, which are typically small in scale, intrusive, time-intensive and costly. In contrast to earlier works, we utilize a non-intrusive methodology to understand green space effects at large-scale and in greater detail, via digital traces left by Twitter users. Using this methodology, we perform an empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Possible explanations for this trend are anticipation for the park visit, meeting friends on the way, or perhaps relief due to leaving work and heading to a more enjoyable location. Recent work found that the emotion of anticipation increases in greenspaces (Lim et al, ); further investigation is merited to better understand the temporal dynamics of anticipation and its relationship with nature contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for this trend are anticipation for the park visit, meeting friends on the way, or perhaps relief due to leaving work and heading to a more enjoyable location. Recent work found that the emotion of anticipation increases in greenspaces (Lim et al, ); further investigation is merited to better understand the temporal dynamics of anticipation and its relationship with nature contact.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we use location‐enabled data from social media to observe individuals at a level of geographical precision that indicates actual contact with greenspace and biodiversity. Previous studies analysing tweets in urban greenspace have studied comparative well‐being across a city, emotional changes across seasons, and different ways of analysing the emotional content of tweets (Lim et al, ; Plunz et al, ; Roberts et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Twitter data analysis is mostly limited in data accessibility, thereby, once the required data is available, the analysis can be performed on scales ranging from intra-urban to even global for any period ranging from a few hours to several years. Recent developments in Geographic Information Systems (GIS)-based social media analysis offer the possibility to explore spatial, temporal and even affective aspects of users' behavior, even for public spaces and park visits [28][29][30]47,48]. However, some of these analyses still have limitations due to the manual interpretation of only a relatively low number of social media posts.…”
Section: The Importance Of Urban Green Areas and Ways To Analyze Theimentioning
confidence: 99%
“…After the algorithm assigned a value to each of these new attributes, we compared whether there is a difference between park tweets and non-park tweets. Based on previous studies (e.g., [47]) the hypothesis was that park tweets could be more positive. However, our results only partially confirm this.…”
Section: Sentiments and Emotionsmentioning
confidence: 99%
“…It has recently been shown that the physical environment can also influence thought content and valence (Lim et al, 2018;MacKerron & Mourato, 2013;Schertz et al, 2018). This may be one pathway for these effects, as thoughts in turn can influence mood and behavior (Killingsworth & Gilbert, 2010;Pennebaker & Beall, 1986).…”
Section: Visual Features and Thought Contentmentioning
confidence: 99%